Environmental impacts of infrastructure upgrading as transportation hub: a case study of KLIA 2 - Sahrir, Syazwani; Bachok, Syahriah; Mohamed Osman, Mariana (2013)
The paper describes the malaysian experiences with airport expansion. In malaysia, the rise of low cost air travel has had the government revising the current capacity of the international airport provision. The research relates the experiences of major expansion phases of the Kuala Lumpur International Airport 2 (KLIA2), the second budget airline airport to support the current international airport in Malaysia. Some of major environmental concerns in airports development are noise levels, local air quality, ground and surface water and soil quality, recycling and sustainability as well as the loss of habitat and wildlife in the area. The research identified several sample locations within the study area and also the surrounding area. The sample locations selected based on the intensity of the development within the sites and the severity of the land use changes. Various airborne particulate matter samplers and sound level meter used to record both noise and particulate matter levels. The findings suggested that increased intensity of construction activities and land use changes had direct relationships with the noise and particulate matter levels. The findings of the study hoped to assist in providing a better insight into the intangible costs and benefits derived from an airport expansion.